A rover's story - Warga, Jasmine (Balzer + Bray, 2022)
Resilience is a Mars rover built to explore the Red Planet. He's a robot but as he learns new things from the NASA scientists who assemble him, he begins to develop human-like feelings. Finally, Res sets off for Mars with a friendly drone helicopter named Fly, and he soon realizes that Mars is a dangerous place filled with dust storms and giant cliffs, but Res is determined to live up to his name and make sure the mission succeeds.